Evaluation of the clientele's attitudes toward the utilization of media materials of the Quezon City Public Library - Carlos, Angeline F. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1994)
The Quezon City Public Library in East Avenue is a library known to have a good collections of print and nonprint materials. In this regard, a study is made to evaluate the collection and services of the above mentioned library.
This study evaluated the media materials and facilities of Quezon City Public Library and the users' attitudes toward the utilization of such library materials.
Questionnaires were used to gather the data necessary to complete this study. Interviews with librarians supplemented the questionnaires given to the users, regardless of their status, (e.g. student, professional, or out-of-school youth).The findings of this study revealed that very few people were aware of the library's present collection. Though the library is known for its extensive collection, the library still needs a lot to improve on its media facilities. The librarians should be thoroughly trained in identifying the different media materials, its functions, storage and maintenance.
Typescript.
Vita.
Thesis (Bachelor of Library Science)--University of the Philippines Diliman
Keywords: Libraries -- Special collections -- Philippines -- Quezon City; Library use studies -- Philippines -- Quezon City; Quezon City Public Library